(untitled) (Fiep Bulletin - online, 2013)
The breathing is covered of a considerable importance in the approach of the manual therapies. The relationship between the breathing mechanics and the cervical column many times is neglectful. Few physiotherapists recognize that the manipulation of the third cervical vertebra can be used as a treatment form with repercussions in several areas. This research aimed to evaluate the influences of the manipulation of the third cervical in the volumes and lung capacities. The study consisted of a sample of 20 academics, among 18 and 24 years, that filled out the inclusion criteria. The academics selected were submitted, firstly, to an espirometria, followed by the manipulation of the third cervical vertebra, soon after to a new espirometria, which was reapplied or re-done half hour after the manipulation. We observed (it gets better) the increase in the volumes and capacities after the cervical manipulation, that stayed even after the accomplishment of the third espirometria. It was concluded this way that the cervical manipulation helps in the improvement of the volumes and lung capacities